2007
DOI: 10.1002/bdd.597
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic interaction between efavirenz and dual protease inhibitors in healthy volunteers

Abstract: The combination of efavirenz with HIV-1 protease inhibitors (PI) results in complex interactions secondary to mixed induction and inhibition of oxidative metabolism. ACTG A5043 was a prospective, open-label, controlled, two-period, multiple-dose study with 55 healthy volunteers. The objective of the present study was to evaluate the potential pharmacokinetic interaction between efavirenz and dual PIs. The subjects received a daily dose of 600 mg efavirenz for 10 days with amprenavir 600 mg twice daily added at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…The majority of studies that have reported long expected half-lives of 40-55 h or more were conducted in health volunteers with data collected over a longer time period [30]. The half-life obtained in this study is similar to that obtained in a study by Ma et al, in which samples were collected over a 12-h period (t 1/2 23-30.8 h) [31], although the protease inhibitor amprenavir was co-administered to the volunteers between days 10 and 14 of the study.…”
Section: Discussionsupporting
confidence: 80%
“…The majority of studies that have reported long expected half-lives of 40-55 h or more were conducted in health volunteers with data collected over a longer time period [30]. The half-life obtained in this study is similar to that obtained in a study by Ma et al, in which samples were collected over a 12-h period (t 1/2 23-30.8 h) [31], although the protease inhibitor amprenavir was co-administered to the volunteers between days 10 and 14 of the study.…”
Section: Discussionsupporting
confidence: 80%
“…demonstrated in healthy volunteers that increased P‐gp activity as measured by Rh123 uptake in lymphocytes correlated with increased apparent oral CL / F and apparent oral V / F , and both were decreased with indinavir exposure . In healthy volunteers, adding PIs to EFV increased V / F but not CL / F for EFV . In another study in HIV‐1 infected volunteers, the concomitant use of EFV or NVP increased the apparent oral clearance of lopinavir by 39%, ( p < 0.001) .…”
Section: Discussionmentioning
confidence: 94%
“…This picture is also additionally complicated by the effects that these agents have on the efflux transporter P‐gp, which could lead to increased F through intestinal transporter–enzyme interplay resulting in a decreased CL / F . Cyclosporine and the PIs themselves are substrates as well as inhibitors of P‐gp and the NNRTIs have differential effects on P‐gp, but are generally thought to act as inducers of this transporter .…”
Section: Discussionmentioning
confidence: 99%
“…The lower limit of quantification (LLOQ) for efavirenz and 8-hydroxyefavirenz were both 5 ng mL -1 at a signal-to-noise (S/N) ratio of 10. This LLOQ value (5 ng mL -1 ) is lower than values previously reported (5-205 ng mL -1 ) [21,22,28,39,40]. In addition, these sensitivities were enough to apply pharmacokinetic studies of efavirenz and its metabolites after oral administration of efavirenz.…”
Section: Validation Resultsmentioning
confidence: 62%
“…Several organic solvents including ethyl acetate [15], methyl-t-butyl ether [27], and hexane/ethyl acetate mixture [28] were previously used to extract efavirenz in plasma samples. Among organic solvents (ethyl acetate, ether, dichloromethane, chloroform and their mixtures) tested, ethyl acetate was found to be optimal, which can produce a clean chromatogram for blank plasma samples and the best recovery, and the least matrix effect.…”
Section: Determination Of Efavirenz and Its Two Metabolitesmentioning
confidence: 99%